2012
DOI: 10.1177/1545968312448232
|View full text |Cite
|
Sign up to set email alerts
|

Lokomat Robotic-Assisted Versus Overground Training Within 3 to 6 Months of Incomplete Spinal Cord Lesion

Abstract: Robotic-assisted training was equivalent to conventional walk training in patients with a variety of nonprogressive spinal cord pathologies for walking speed, but the need for orthotics and assistive devices was reduced, perhaps because of greater leg strength in the robotic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(193 citation statements)
references
References 20 publications
9
181
2
1
Order By: Relevance
“…Israel et al [23], Hunt et al [39], and Jack et al [40] also presented values for peak V O 2 (14,16, and 28 mL/kg/min, respectively) obtained during maximal active robotic walking that were substantially higher than values of the present study (V O 2robot = 6.8 mL/kg/min). During active walking in these studies, subjects were supposed to push against the orthoses with their legs while walking.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Israel et al [23], Hunt et al [39], and Jack et al [40] also presented values for peak V O 2 (14,16, and 28 mL/kg/min, respectively) obtained during maximal active robotic walking that were substantially higher than values of the present study (V O 2robot = 6.8 mL/kg/min). During active walking in these studies, subjects were supposed to push against the orthoses with their legs while walking.…”
Section: Discussioncontrasting
confidence: 53%
“…Speed, BWS, and amount of assistance can be adjusted to individual ability in order to create a challenging environment where patients can practice stepping. Most studies investigating robot-assisted gait training in iSCI focused on the effectiveness of improving neurologic and motor function and concluded that it is an appropriate therapy for improving walking ability [16][17]. Although there is some knowledge with regard to the cardiovascular effects of BWS treadmill training with manual assistance [13,[18][19][20][21], little is documented about the cardiorespiratory effects of robot-assisted gait training.…”
Section: Introductionmentioning
confidence: 99%
“…12,84,87 It also uses a six-point scale for MMT grading, but instead of isolated muscles, it evaluates muscle groups, which should also be determined by the examiner. 103 Another scale applied to MMT grading is that elaborated by the Medical Research Council, 23,50,79,86 as well as its variation, 83 96,99 Electronic search (n=495) Pubmed 12 MMT Daniels and Worthinghan Gomes-Osman; Field-Fote (2015) 13 Manual dynamometer Average of three repetitions 42 Isokinetic dynamometer three maximum voluntary contractions, with 3 to 6s of duration, and 1 minute of rest between them Sledziewski; Schaaf; Mount (2012) 43 MMT UEMS Alcobendas-Maestro et al (2012) 44 MMT LEMS 101 MMT Brunnstron e Dennen which grades strength on a scale of 0 to 5. It does not define the resistance that must be applied by the examiner at the time of the test, nor does it consider the range of motion developed.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 and Figure 1 show the reporting of each CONSORT item. The median (IQR) number of CONSORT items per trial that was 'fully reported' was 11/37 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The median (IQR) number of CONSORT items per trial that was either 'fully reported' or 'not relevant' or 'not reported but unable to determine if relevant/done' was 20/37 items (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%